2003
DOI: 10.1002/tcr.10046
|View full text |Cite
|
Sign up to set email alerts
|

Alkyl chains acting as entropy reservoir in liquid crystalline materials

Abstract: The roles played by the conformational disordering of alkyl chains in determining the aggregation states of matter are reviewed for liquid crystalline materials from a thermodynamic perspective. Entropy, which is one of the most macroscopic concepts but which has a clear microscopic meaning, provides crucial microscopic information for complex systems for which a microscopic description is hard to establish. Starting from structural implication by absolute (third-law) entropy for crystalline solids, the existe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
77
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 81 publications
(78 citation statements)
references
References 71 publications
(129 reference statements)
0
77
0
1
Order By: Relevance
“…10 J K ¹1 (mol of CH 2 ) ¹1 ). 19,20 On the other hand, a much smaller slope (ca. 5 J K ¹1 (mol of CH 2 )…”
Section: 3mentioning
confidence: 99%
See 3 more Smart Citations
“…10 J K ¹1 (mol of CH 2 ) ¹1 ). 19,20 On the other hand, a much smaller slope (ca. 5 J K ¹1 (mol of CH 2 )…”
Section: 3mentioning
confidence: 99%
“…2,3 Indeed, the present authors have shown that the large entropy capacity, in some cases, governs the phase sequence against temperature variation. 18,19,2123 Considering that equilibrium is characterized by the minimum Gibbs energy, the large contri- bution of the chain entropy strongly suggests that the molten state is not an accidental situation but the prerequisite for the appearance of most real liquid-crystalline mesophases as stable phases because most mesogens have flexible chain(s) at the end(s) of the core. Indeed, no simple molecular model has been reported for SmE phase to the authors' knowledge.…”
Section: ¹1mentioning
confidence: 99%
See 2 more Smart Citations
“…However, the experimental confirmation through the analyses of entropy itself were performed only recently. 16,17 Indeed, the molten state of chain in LC states were established through the analysis of absolute entropy for some mesogens showing cubic LC phases such as 4 -alkyloxy-3 -nitrobiphenyl carboxylic acid (ANBC(n), Fig. 1).…”
Section: Introductionmentioning
confidence: 99%